Pengaruh Zakat, Islamic Corporate Social Responsibility (ICSR), Ukuran Perusahaan, dan Reputasi Bank terhadap Kinerja Keuangan Bank Umum Syariah di Indonesia - Nufidatul Mahmudah (Journal of Innovative and Creativity, 2026)
This study aims to analyse the effect of zakat, Islamic Corporate Social Responsibility (ICSR), company size, and bank reputation on the financial performance of Islamic Commercial Banks in Indonesia. This study is based on Shariah Enterprise Theory, Stakeholder Theory, and Legitimacy Theory, which emphasise the importance of fulfilling shariah and social responsibilities in improving sustainable financial performance. The research sample consists of Islamic Commercial Banks in Indonesia for the period 2019–2024. Data were obtained from the banks' annual reports and sustainability reports, then analysed using multiple linear regression. The results show that, partially, zakat and ICSR have a positive and significant effect on the financial performance of Islamic Commercial Banks, while company size and bank reputation do not have a significant partial effect. However, zakat, ICSR, company size, and bank reputation simultaneously have a significant effect on financial performance. Based on these findings, this study recommends that Islamic Commercial Banks improve the management of zakat and the implementation of ICSR in a consistent and transparent manner as a strategy to strengthen financial performance and business sustainability.